2006
DOI: 10.1111/j.1460-2466.2006.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Theory in Developing Effective Health Communications

Abstract: This study attempts to show the relevance of behavioral theory for developing communications designed to promote healthy and/or to prevent or alter unhealthy behaviors. After describing an integrative model of behavioral prediction, the model's implications for designing persuasive communications are considered. Using data from a study on smoker's intentions to continue smoking and to quit, it is shown how the theory helps identify the critical beliefs underlying these or other intentions. Finally, it is argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
480
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 688 publications
(505 citation statements)
references
References 39 publications
(45 reference statements)
11
480
0
14
Order By: Relevance
“…Correlations varied between 0.30 and 0.40 depending on the measures used and the subgroups under examination. Fishbein (2000), and Fishbein and Cappella (2006) both saw personality characteristics as indirect predictors of risky driving behavior. Ulleberg and Rundmo (2003) considered the relationship to be indirect.…”
Section: Hypothesesmentioning
confidence: 97%
“…Correlations varied between 0.30 and 0.40 depending on the measures used and the subgroups under examination. Fishbein (2000), and Fishbein and Cappella (2006) both saw personality characteristics as indirect predictors of risky driving behavior. Ulleberg and Rundmo (2003) considered the relationship to be indirect.…”
Section: Hypothesesmentioning
confidence: 97%
“…As such, a number of positive and negative correlates at the personal and socio-contextual level (e.g., achievement goal orientations, moral values, social norms) have been identified. In line with health-related behavior research, most studies in the doping field have adopted the theory of planned behavior (TPB) [13,14] as a broader theoretical background to examine the psycho-social mechanisms that may lead to doping in sport. In this theory, behavior is viewed as a distal or proximal outcome of 1) intention, 2) attitude, 3) subjective norm, and 4) perceived behavioral control.…”
Section: Introductionmentioning
confidence: 99%
“…smoking), showing that the addition of new constructs (i.e., descriptive norms, situational temptation) improves the predictive ability of the TPB model, and c) recent arguments suggesting the use of integrative approaches [14,20] to incorporate distal predictors of behavior (e.g., sportspersonship, moral disengagement, or achievement goals in the case of doping) and demographics. As an example of such new approaches, Lucidi et al [17] measured participants' moral disengagement (i.e., disassociating oneself from the moral implications of one's unethical actions) and showed that this variable predicted doping intentions and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that IVET can keep participants motivated while exercising, potentially enhancing exertion and intensity as well as long-term adherence. Although these treatments were successful, they did not incorporate relevant theoretical constructs that may influence health-related outcomes (Fishbein & Cappella, 2006). Theories of health behavior change may help create more powerful stimuli.…”
Section: Ivet and Psychological Researchmentioning
confidence: 99%